Pengaruh Limbah Tutup Botol Air Mineral Pada Lapis Perkerasan Base A - Sigit Harianto; Sazuatmo Sazuatmo; Elly Tripujiastutie (MAJALAH TEKNIK SIMES, 2023)
One of the wastes that can be used as additives in base A is mineral water bottle caps. This waste can be expected to reduce the use of natural materials and reduce the amount of plastic waste. This study aims to determine the CBR value after adding mineral water bottle cap" waste as much as 6%, 8%, 10%, 12%, and 14%. The method used is a laboratory CBR test method using a CBR penetration tool to obtain the results of the experiment. The results of this "study indicate that base A aggregate added with 6% of mineral water bottle cap waste produces a CBR value of 96.85%, the addition of 8% produces a CBR value of 98.88%. The addition of 10% produces a CBR value of 99.68%, the addition of 12% produces a CBR value of 98.29% and the" addition of 14% produces a CBR value of 97.09%. These results indicate that the addition of plastic bottle cap waste as a filler in base A can be used because the CBR value is greater than "90% and with the composition that has been determined in this study.